(untitled) (Heritage, 2020)
Evaluation of the essayistic opus of Danilo Kiš and his authorial choices, if we exclude one scientific paper by R. Ivanović, dedicated to the book Po-ethics, has not been the subject of a serious discussion so far, although the critics mostly agreed that he is a world writer. The subject of interest of this paper are the selections of essay texts that Kiš published during his lifetime in the books Po-ethics (1972), Po-ethics, book two (1974) and Homo poeticus (1983). The research focus is on the composition and structure of books – criteria for the selection and arrangement of texts, the logic of their content, the level of authorial self-criticism and representativeness. When making a judgment about the objectivity of Kiš as the compiler of these selections, essays that for various reasons remained outside the covers of the mentioned books are also taken into consideration – their literary-aesthetic, cognitive, cultural and autopoetic value. The composition of the book Anatomy Lesson, although in the genealogical sense it is a book-essay, deserves a special study, and therefore is not the subject of analysis of this paper. Key words: essay writing, selection, criterion, self-criticism, representativeness, evaluation, Po-ethics (1972), Po-ethics, book two (1974), Homo poeticus (1983)